2021
DOI: 10.3390/molecules26123730
|View full text |Cite
|
Sign up to set email alerts
|

Further Validation of Quantum Crystallography Approaches

Abstract: Quantum crystallography is a fast-developing multidisciplinary area of crystallography. In this work, we analyse the influence of different charge density models (i.e., the multipole model (MM), Hirshfeld atom refinement (HAR), and the transferable aspherical atom model (TAAM)), modelling of the thermal motion of hydrogen atoms (anisotropic, isotropic, and with the aid of SHADE or NoMoRe), and the type of radiation used (Mo Kα and Cu Kα) on the final results. To achieve this aim, we performed a series of refin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Moreover, our research on quantum crystallography methods showed that quantum crystallography models may be used for the reconstruction of the electron density. The methodological correctness of this approach was proved by us in our previous studies [ 14 , 15 ]. Therefore, in this work we additionally present results of reconstruction of charge density of final crystal structures of vitamin D analogues (PRI-1730 and PRI-1731, Figure 2 ) which were obtained using the transferable aspherical atom model (TAAM).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, our research on quantum crystallography methods showed that quantum crystallography models may be used for the reconstruction of the electron density. The methodological correctness of this approach was proved by us in our previous studies [ 14 , 15 ]. Therefore, in this work we additionally present results of reconstruction of charge density of final crystal structures of vitamin D analogues (PRI-1730 and PRI-1731, Figure 2 ) which were obtained using the transferable aspherical atom model (TAAM).…”
Section: Introductionmentioning
confidence: 95%
“…This study is also an example that quantum crystallography methods may be used for the refinement of low-resolution data even when the quality of the data is not very high (in terms of measurement statistics and data resolution). When we performed the methodological work to prove this approach, we used the model compounds which did not exceed 25 atoms [ 14 , 15 ]. On the contrary, vitamin D analogues have more than 70 atoms.…”
Section: Introductionmentioning
confidence: 99%
“…We have compared these (Table 1) using values from the similarity index S 12 (see the supporting information for definitions of the descriptors) as introduced by Whitten & Spackman (2006), an average absolute difference and relative difference in ADP tensor components. It has been suggested that very good agreement for ADP values was achieved for S 12 that is equal to or smaller than 1 with an in-house source measurement refined with HAR (Wanat et al, 2021). Good agreement between X-ray and neutron structures should not be taken for granted as HAR is very sensitive to the quality of the X-ray data.…”
Section: O Ice VImentioning
confidence: 99%
“…This is an iterative procedure, where 'tailor-made' aspherical atomic scattering factors (Hirshfeld, 1977), obtained by quantum mechanical methods, are used to refine the atomic positions and ADPs in the standard, least-squares structure refinement until convergence. Previous work reported that HAR provides more accurate hydrogen atom positions (Woin ´ska et al, 2016(Woin ´ska et al, , 2021Malaspina et al, 2020) than IAM and enables refinement of hydrogen ADP values (Wanat et al, 2021). Furthermore, HAR utilizing relativistic Hamiltonians was also successfully applied to heavy elements (Pawle ˛dzio et al, 2021;Buc ˇinsky ´et al, 2019Buc ˇinsky ´et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%